The association of caries severity with children's quality of life at TK Bersama Ceria Delitua - Purba, Member Reni; Erawati, Suci; Sinurat, Ariel Oertega (Buletin Kedokteran & Kesehatan Prima, 2025)
Oral and dental health is a component of overall health that can significantly impact a child's quality of life. Dental caries is a major oral health problem among preschool children. This study aimed to determine the relationship between the severity of dental caries and the quality of life of children attending TK Bersama Ceria Delitua kindergarten. This analytical survey employed a cross-sectional design. The study population consisted of all children enrolled. A sample size of 30 participants was selected using purposive sampling. Data collection was conducted through questionnaires and dental examinations. Data analysis was performed using Spearman's rank correlation coefficient. The mean decay (d) score was 5.47 ± 2.474, the mean extraction (e) score was 0.80 ± 1.064, and the mean filling (f) score was 0.13 ± 0.434. The overall mean def-t score was 6.40 ± 2.908. The mean child quality of life, as measured by the Early Childhood Oral Health Impact Scale (ECOHIS), was 46.43 ± 7.873. Spearman's correlation analysis revealed a significant positive correlation between the severity of dental caries and children's quality of life (p = 0.003; r = 0.521), indicating a strong relationship. The study concludes that a higher def-t score is associated with a poorer quality of life in children.